(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Infertility is defined as when a couple failed to conceive within one or more years of regular unprotected coitus. Primary infertility denotes those patients who have never conceived. Secondary infertility denotes previous pregnancy but failure to conceive subsequently. 80% of the couples achieve conception if they so desire, within one year of having regular intercourse with adequate frequency. Another 10% will achieve the objective by the end of second year. As such, 10% remain infertile by the end of second year. Now days, PCOS is one of the most common cause of infertility in women. In PCOS the hormonal imbalance interferes with the development and release of ovum from the ovaries. PCOS manifested by amenorrhoea, hirsutism and obesity associated with enlarged polycystic ovaries. PCOS is characterised by excessive androgen production by ovaries and adrenals which interferes with growth of the ovarian follicles. Therefore PCOS is a state of androgen excess and chronic anovulation. A 27 years old female visited OPD of PTSR NIA with complaints of wants issue since two years. After thorough examination, she was diagnosed as PCOS in Ultrasonography. At first, medicine for withdrawal bleeding was given. Then Shatapushpa churna and Phalasarpi was given for two months and then after she was conceived.